Pretargeted Imaging and Radioimmunotherapy of Cancer Using Antibodies and Bioorthogonal Chemistry - van de Watering, Floor C. J.; Rijpkema, Mark; Robillard, Marc; Oyen, Wim J. G.; Boerman, Otto C. (Frontiers in Medicine, 2014)
Selective delivery of radionuclides to tumors may be accomplished using a two-step approach, in which in the first step the tumor is pretargeted with an unlabeled antibody construct and in the second step the tumor is targeted with a radiolabeled small molecule. This results in a more rapid clearance of the radioactivity from normal tissues due to the fast pharmacokinetics of the small molecule as compared to antibodies. In the last decade, several pretargeting approaches have been tested which have shown improved tumor-to-background ratios and thus improved imaging and therapy as compared to directly labeled antibodies. In this review we will discuss the strategies and applications in (pre-)clinical studies of pretargeting concepts based on the use of bispecific antibodies, which are capable of binding to both a target antigen and a radiolabeled peptide. So far, three generations of the bispecific antibody-based pretargeting approach have been studied. The first clinical studies have shown the feasibility and potential for these pretargeting systems to detect and treat tumor lesions. However, to fully integrate the pretargeting approach in clinic, further research should focus on the best regime and pretargeting protocol. Additionally, recent developments in the use of bioorthogonal chemistry for pretargeting of tumors suggest that this chemical pretargeting approach is an attractive alternative strategy for the detection and treatment of tumor lesions.